Climate change decouples marine and freshwater habitats of a threatened migratory fish. Issue 7 (24th May 2017) - Lin, Hsien‐Yung; Bush, Alex; Linke, Simon; Possingham, Hugh P.; Brown, Christopher J.
Abstract: Aim: To assess how climate change may decouple the ecosystems used by a migratory fish, and how decoupling influences priorities for stream restoration. Location: Australia. Methods: We modelled changes in habitat suitability under climate change in both riverine and marine habitats for a threatened diadromous species, the Australian Grayling Prototroctes maraena, using niche models. The loss of riverine habitats for Grayling was compared with or without considering the impact of climate change on adjacent marine habitats. We also asked whether considering marine climate change changed the locations where removing dams had the greatest benefit for Grayling conservation. Results: Climate change is expected to cause local extinction in both marine and river habitats regardless of whether dams are retained or removed at the trailing edge of the Grayling's range (north‐eastern). Decoupling of habitats was most apparent in the eastern and south‐eastern portion of the Grayling's range, where ocean warming may cause a decline in the suitability of marine habitats for larvae, while many freshwater habitats retained suitable habitat for adults. Removing dams to restore connectivity between ocean and freshwater habitats was predicted to have the greatest benefit for Grayling in southern portions of their range. Under climate change, the priorities for barrier removal gradually shift towards dams at higher elevation because of increasing suitability of freshwater habitats at higher elevations. Main conclusions: Our study highlights the importance of assessing climate range shifts in multiple ecosystems for migratory species and can help inform priorities for stream restoration under a changing climate.